Clima e forma urbana: métodos de avaliação do efeito das condições climáticas locais nos graus de conforto térmico e no consumo de energia elétrica em edificações - Lima, Lucimeire Pessoa de (2005)
Cities can deeply modify natural environment. Buildings, removal of natural soil, emissions and heat generation modify urban climate. Consequently, energy consumption for air-conditioning is directly related to local climate. The purpose of this dissertation is to analyze the relation between urban form and energy consumption for air-conditioning in buildings, in order to ensure indoor comfort conditions. The theoretical survey presents considerations regarding urban settlements over human history, emphasizing urban planning experiences. Issues related to human interaction with natural environment, technology and population growth, concentrated in urban areas, are also discussed. A brief overview is shown, concerning climate, urban climatology and its relation to urban planning and to heat island formation and to sustainability. The study comprehends 4 different methods relating urban form to temperature distribution in different locations of Curitiba, and, as a consequence, to energy consumption for space conditioning of buildings. The first method included height and albedo parameters to the analysis of data, gathered at different monitoring locations of Curitiba in 2002. The second method considered consumption calculations from hourly predictions of the indoor temperature in 3 lowcost houses, monitored in a previous study, assuming these were located at different sites of the city. The third method took into account predictive formulas, estimating indoor temperatures for the same houses and resulting energy consumption. The fourth method used computer simulations with the design tool COMFIE, in order to generate indoor temperature curves in one of these houses, therefore evaluating resulting energy consumption. Finally, some considerations regarding the applied methods are presented.